Impact of Pretransplant Antimicrobial Sulfonamide Allergy Label in Kidney Transplant Recipients - Powers, Harry Ross; Wadei, Hani M.; Cuellar, Cesar Campos; Venugopal, Amogharvasha; Pleqi, Vasili; Hochwald, Alex; Ma, Yaohua; Gonzales, Alexei (Transplant infectious disease, 2025)
Sulfa antibiotic allergy labels (SALs) are encountered frequently in kidney transplant recipients (KTs). This often results in patients receiving second-line prophylaxis for both Pneumocystis jiroveci and urinary tract infections (UTIs). The effect of SAL on outcomes including UTIs after KT is unclear. In our single-center retrospective cohort study, we investigated the effect of SALs on bacteriuria after KT. We identified patients with pre-KT SALs from 2011 to 2022. A matched cohort was then created using KT with no pretransplant SALs. The groups were compared using proportional analysis and univariable and multivariable Cox proportional regression models. The primary outcome of interest was the proportion of individuals experiencing one or more episodes of bacteriuria within 1 year posttransplant. Secondary outcomes included bacteremic UTIs, acute kidney injury, and opportunistic infections. We found that the proportion of individuals experiencing bacteriuria within the first-year posttransplant was significantly greater in the SAL group versus the control group (n = 21, 28% vs. n = 22, 14.7%, p = 0.012). This result was also seen in univariable and multivariable survival analysis. In addition, episodes of UTI with associated bacteremia (n = 11, 14.7% vs. n = 5, 3.3%, p = 0.002) were statistically significantly higher in the SAL group. There was a significantly greater number of episodes of bacteriuria in the first-year posttransplant in subjects with pretransplant SAL. Based on our findings, we suggest that all KTs with pretransplant SALs undergo evaluation and intervention prior to transplantation.